Comparative analysis of the amount of postoperative drainage after intraoral vertical ramus osteotomy and sagittal split ramus osteotomy - Kim, Hyunyoung (The Korean Association of Oral and Maxillofacial Surgeons, 2014)
OBJECTIVES: The purpose of this retrospective study was to compare the amount of postoperative drainage via closed suction drainage system after intraoral vertical ramus osteotomy (IVRO) and sagittal split ramus osteotomy (SSRO). MATERIALS AND METHODS: We planned a retrospective cohort study of 40 patients selected from a larger group who underwent orthognathic surgery from 2007 to 2013. Mean age (range) was 23.95 (16 to 35) years. Patients who underwent bilateral IVRO or SSRO were categorized into group I or group II, respectively, and each group consisted of 20 patients. Closed suction drainage system was inserted in mandibular osteotomy sites to decrease swelling and dead space, and records of drainage amount were collected. The data were compared and analyzed with independent t-test. RESULTS: The closed suction drainage system was removed at 32 hours postoperatively, and the amount of drainage was recorded every 8 hours. In group I, the mean amount of drainage was 79.42 mL in total, with 31.20 mL, 19.90 mL, 13.90 mL, 9.47 mL, and 4.95 mL measured at 0, 8, 16, 24, and 32 hours postoperatively, respectively. In group II, the mean total amount of drainage was 90.11 mL, with 30.25 mL, 25.75 mL, 19.70 mL, 8.50 mL, and 5.91 mL measured at 0, 8, 16, 24, and 32 hours postoperatively, respectively. Total amount of drainage from group I was less than group II, but there was no statistically significant difference between the two groups (P=0.338). There was a significant difference in drainage between group I and group II only at 16 hours postoperatively (P=0.029). CONCLUSION: IVRO and SSRO have different osteotomy design and different extent of medullary exposure; however, our results reveal that there is no remarkable difference in postoperative drainage of blood and exudate.